2004
DOI: 10.1541/ieejeiss.124.1478
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Reinforcement Learning System with Time-Varying Parameters

Abstract: In this paper, an evolutionary reinforcement learning system with time-varying parameters that can learn appropriate policy in dynamical POMDPs is proposed. The proposed system has time-varying parameters that can be adjusted by using reinforcement learning. Hence, the system can adapt to the time variation of the dynamical environment even if its variation cannot be observed. In addition, the state space of the environment is divided evolutionarily. So, one need not to divide the state space in advance. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, the learning systems proposed so far employ fixed learning parameters, and it is difficult to handle time-varying parameters. This study deals with such dynamical POMDP environments in which time changes cannot be observed, and proposes an appropriate learning method [9,10]. The proposed system employs learnable time-varying parameters, and thus is easily applicable to dynamical environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the learning systems proposed so far employ fixed learning parameters, and it is difficult to handle time-varying parameters. This study deals with such dynamical POMDP environments in which time changes cannot be observed, and proposes an appropriate learning method [9,10]. The proposed system employs learnable time-varying parameters, and thus is easily applicable to dynamical environments.…”
Section: Introductionmentioning
confidence: 99%